KAJIAN TENTANG SISTEM PENDETEKSIAN SEL DARAH PUTIH DENGAN METODE EIGEN WINDOW - Anthony Domenico; Lina Lina; Arlends Chris (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
We developed a white blood cell detection system using Eigen window method. The input Data used in the program is a file image with RGB color level with the format of the bitmap image (.bmp). The extraction stage used the PCA method applied to several small windows. The main target of the system is to detect the location of the white blood cells in a given blood cell pictures